NCMP-15. BEVACIZUMAB FOR THE TREATMENT OF CEREBRAL RADIATION NECROSIS: A RETROSPECTIVE COHORT STUDY. (11th November 2019) - Luitse, A; Dankbaar, Jan; De Vos, Filip; Fonville, Susanne; Robe, Pierre; Seute, Tatjana; Verhoeff, Joost; Snijders, Tom
Abstract: BACKGROUND: Cerebral radiation necrosis (RN) is a critical complication of radiotherapy for brain tumors. Treatment with corticosteroids provides suboptimal symptom relief, and may have considerable side effects. Small-scale studies support the use of bevacizumab, but systematic data from clinical practice on its efficacy and toxicity remain scarce. METHODS: In this retrospective cohort study, we included consecutive patients with symptomatic RN that underwent treatment with bevacizumab in our academic neuro-oncology clinic. RN was diagnosed based on imaging, histology or both. The primary outcomes were reported neurological improvement during follow-up, the duration of response, the reported improvement on MRI, and radiological outcome according to RANO criteria. Other outcomes included reduction of dexamethasone dose and the occurrence of adverse events. RESULTS: Of the 37 included patients (39 RN-episodes), the majority had a glioblastoma (n = 22) or other diffuse glioma (8), followed by brain metastases (4) or other (3). Clinical response was reported in 17 RN-episodes (43.6%) and lasted for a median of 13 weeks (IQR 6–32 weeks). Radiological improvement during follow-up was reported in 29 RN-episodes (80.6%). RANO-defined radiological responses included 1 complete response (3.4%), 7 partial responses (24.1%), 1 minor response (3.4%) and 17 stable disease (58.6%). In total, 36 adverse events occurred, most commonly venous thrombo-embolism, hypertension and dyspnea, with 8 grade III-IV complications and 2 deaths (grade V) which were possibly related to bevacizumab. Of 32 patients on dexamethasone, 9 (28.1%) had completely stopped its use at treatment cessation. CONCLUSION: This observational study confirms that patients with cerebral RN can benefit both clinically and radiologically from bevacizumab treatment in a real-life clinical setting, although our results are more modest than previous literature suggests. The high prevalence of – sometimes severe – adverse events should be weighed against the possible clinical benefit when counselling patients about this treatment option.